Demographic projections by religion and education in India - Stonawski, Marcin; Potančoková, Michaela; Skirbekk, Vegard (Studia Demograficzne, 2015)
Studying religion jointly with education allows one to produce more precise projections of the size and structure of religious communities. India’s religious groups are characterized by large differences in their education and fertility levels. Among those with secondary or more education, there tends to be low variation in fertility, while for those without any education, fertility is high and varies substantially. For India, if fertility differentials were constant and there was no increase in educational enrolment, the Indian population would grow from 846 million in 2000 to more than 2.3 billion in 2050, while the Hindu population would change from 80.2% to 76.4% and the proportion of Muslims would rise from 13.4% to 19%. If fertility converges and education levels increases, the population would increase to 1.7 billion by 2050, with 78.2% Hindus and 16.5% Muslims.